2011
DOI: 10.1111/j.1439-0531.2011.01947.x
|View full text |Cite
|
Sign up to set email alerts
|

Derivation, Characterization and Differentiation of Buffalo (Bubalus bubalis) Amniotic Fluid Derived Stem Cells

Abstract: Amniotic fluid cells (AFCs) are obtained from amnion for pre-natal analysis and can be cultured in vitro. Heterogeneous amniotic fluid (AF) contains various cell types, and it is believed that some of these cells possess the stem cell properties. The aim of this study was to characterize these cells by phenotypical and genotypical means in buffalo. The differentiation potential of amniotic fluid stem (AFS) cells was carried out by converting these cells into neurons. The AFCs were cultured without feeder cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
22
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 48 publications
4
22
0
Order By: Relevance
“…Dev et al. () reported similar results, but with buffalo AFC cultures. These researchers also reported that after 6 days of culture, cells from the same amniotic fluid sample were found with different shapes: star‐shaped, spherical‐shaped with and without nucleus, pentagonal‐shaped and round‐shaped.…”
Section: Discussionsupporting
confidence: 52%
See 2 more Smart Citations
“…Dev et al. () reported similar results, but with buffalo AFC cultures. These researchers also reported that after 6 days of culture, cells from the same amniotic fluid sample were found with different shapes: star‐shaped, spherical‐shaped with and without nucleus, pentagonal‐shaped and round‐shaped.…”
Section: Discussionsupporting
confidence: 52%
“…The use of cells from extra‐embryonic tissues, umbilical cord and amniotic fluid can lead to significant advances in cell therapy, animal production and conservation (Dev et al. ). Extra‐embryonic tissues that originate from the hypoblast and trophectoderm do not participate in gastrulation and are therefore less differentiated than adult somatic cells (Cremonesi et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Expression of these pluripotency marker genes has previously been reported in amnion-derived cells of various mammalian species including rat (Marcus et al 2008), canine (Park et al 2012), chicken (Gao et al 2012), buffalo ) and human (Miki et al 2005). The expression of these genes has also been reported positive in cells derived from umbilical cord of porcine, equine and buffalo (Carlin et al 2006;Cremonesi et al 2008;Singh et al 2013) and buffalo amniotic fluid (Yadav et al 2011;Dev et al 2012).…”
Section: Discussionmentioning
confidence: 82%
“…Chromosomal spreads at passage 5 and passage 10 revealed that these cells had normal number of chromosomes (2n=50) indicating no apparent changes in ploidy during culture. Previous studies also reported a stable karyotype in cells derived from early buffalo gestation placental tissues (Yadav et al 2011;Dev et al 2012;Mann et al 2013;Singh et al 2013) and term amnion in equine (Seo et al 2013).…”
Section: Discussionmentioning
confidence: 83%